Chronic CRF(1) Receptor Blockade Reduces Heroin Intake Escalation and Dependence-Induced Hyperalgesia - Park, Paula E. (2013)
Opioids represent effective drugs for the relief of pain, yet chronic opioid use often leads to a state of increased sensitivity to pain that is exacerbated during withdrawal. A sensitization of pain-related negative affect has been hypothesized to closely interact with addiction mechanisms. Neuroadaptive changes occur as a consequence of excessive opioid exposure, including a recruitment of corticotropin-releasing factor (CRF) and norepinephrine (NE) brain stress systems. To better understand the mechanisms underlying the transition to dependence, we determined the effects of functional antagonism within these two systems on hyperalgesia-like behavior during heroin withdrawal utilizing models of both acute and chronic dependence. We found that passive or self-administered heroin produced a significant mechanical hypersensitivity. During acute opioid dependence, systemic administration of the CRF1 receptor antagonist MPZP (20 mg/kg) alleviated withdrawal-induced mechanical hypersensitivity. In contrast, several functional adrenergic system antagonists (clonidine, prazosin, propranolol) failed to alter mechanical hypersensitivity in this state. We then determined the effects of chronic MPZP or clonidine treatment on extended access heroin self-administration and found that MPZP, but not clonidine, attenuated escalation of heroin intake, whereas both drugs alleviated chronic dependence-associated hyperalgesia. These findings suggest that an early potentiation of CRF signaling occurs following opioid exposure that begins to drive both opioid-induced hyperalgesia and eventually intake escalation.